The Relationship Between Sedentary Lifestyle and Body Mass Index (BMI) in Students at ITSK RS Dr Soepraoen Malang - Jufiya, Mayang; Mashitah, Musthika Wida; Aminah, Tien (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2025)
A sedentary lifestyle is characterized by a consistent lack of physical activity, which is associated with an increased risk of being overweight and obese. Students often exhibit low levels of physical activity due to academic obligations, which can potentially lead to an increase in their body mass index (BMI). This study aims to examine the relationship between sedentary lifestyle levels and BMI among students at ITSK Dr Soepraoen Hospital in Malang. This study employed a cross-sectional design utilizing quantitative methods. Sampling was conducted through purposive sampling, involving 575 active students across levels 1 to 4. Data were collected using the Sedentary Behaviour Questionnaire (SBQ) in conjunction with BMI measurements. The data analysis was performed using the Chi-Square test. The findings indicated a statistically significant relationship between sedentary lifestyle levels and BMI (p = 0.037). The prevalence of overweight was documented at 11.6% within the low sedentary group, rising to 16.3% in the moderate sedentary group and ultimately reaching 25.2% in the high sedentary group. These results suggest that, despite the statistical significance of the relationship, a sedentary lifestyle remains a considerable factor influencing students' nutritional status. In conclusion, it is essential to implement promotional initiatives that enhance students' awareness of the importance of physical activity in reducing the risk of overweight.